Non-professional phagocytosis of senescent cancer cells revealed in a 3D-bioprinted model of an irradiated lung tumour - Parul Yadav; Pritiranjan Mondal; Sibani Jani; Deepak K. Saini; Kaushik Chatterjee (Virtual and Physical Prototyping)
Three-dimensional (3D) scaffolds represent a transformative tool for studying physiological processes in health and disease contexts by mimicking in vivo conditions that two-dimensional (2D) culture systems cannot capture. This study explores the application of extrusion-based 3D bioprinting technology to create complex scaffolds mimicking the microenvironment of senescent cancer cells induced by radiotherapy. Using a viscoelastic hydrogel bioink composed of a blend of alginate and gelatin, we fabricated scaffolds with porosity and mechanical properties appropriate for culturing lung cells. We then delve into co-culture experiments to understand the cell-cell interactions between spatially patterned populations of normal bronchial epithelial cells (BEAS-2B) and senescent or non-senescent bronchial adenocarcinomic epithelial cells (A549). Normal epithelial cells exhibited non-professional phagocytic activity toward the cancer cells, markedly enhanced when senescence was induced in the cancer cells upon irradiation. As interest in non-animal models grows, these findings underscore the potential of 3D bioprinted platforms to serve as robust alternatives for preclinical research.Created with BioRender.com